Quantum Attraction of Kyai’s Leadership in Indonesian Pesantren - Zamroni Zamroni; Akmal Mundiri; Hanifatur Rodiyah (Dinamika Ilmu, 2022)
The inherent characteristics in a kyai become the primary source of the kyai's power in influencing his followers. One of kyai’s strong characteristics is the Quantum attraction. The leadership of the kyai with a quantum attraction approach can be referred as kyai’s simple action which can be very impactful for his followers. One of these approaches is carried out by kyai at the pesantren Nurul Jadid Paiton Probolinggo. With this approach, the figure of the kyai raises several forms of Quantum attraction behavior that can be used as role models by students as followers. The aim of this research is to understand the primary characteristics of kyai based on quantum attraction. The researcher in this study used a qualitative approach to the type of phenomenology. For data collection, researchers used observation, in-depth interviews, and documentation. The data analysis methods used by the researchers are data reduction, data presentation, and verification. This study indicates that the main characteristics of the leadership behavior of clerics based on quantum attraction are sincere, tawadhu, zuhud, pious, and waro' behaviors and attitudes.